2008
DOI: 10.1111/j.1365-2702.2008.02450.x
|View full text |Cite
|
Sign up to set email alerts
|

A family caregiver‐oriented discharge planning program for older stroke patients and their family caregivers

Abstract: This caregiver-oriented discharge planning program, with its emphasis on individualised health education and home visits following discharge may improve caregivers' preparation and the satisfaction of their needs during the discharge transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 38 publications
2
73
2
3
Order By: Relevance
“…Thus, our CFA was based on the factorial structure of prior psychometric work performed in other populations. Although prior studies showed that the CPS items reflect stroke-caregiver preparedness, 25e27 and contrasting group validity of the CPS in this population is supported, 58 additional studies may be required for further validity testing. Given that some stroke survivors have physical and psychological disability, more dimensions or specific items may be needed to construct a model of preparedness in caregivers of stroke survivors.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, our CFA was based on the factorial structure of prior psychometric work performed in other populations. Although prior studies showed that the CPS items reflect stroke-caregiver preparedness, 25e27 and contrasting group validity of the CPS in this population is supported, 58 additional studies may be required for further validity testing. Given that some stroke survivors have physical and psychological disability, more dimensions or specific items may be needed to construct a model of preparedness in caregivers of stroke survivors.…”
Section: Discussionmentioning
confidence: 77%
“…Skill building and psycho-educational 25,27,28,[30][31][32]35,40,41,[46][47][48]50,53,54,60,63 12 (37. 25,26,29,31,32,34,39,[41][42][43]47,48,52,56,58,59,61,62 15 (46.9) 9 (60) 11 ( Face-to-face and telephone 27,28,30,33,[35][36][37]40,[44][45][46]51,53,54,57,63 13 ( …”
Section: Summary and Best-designed Studiesmentioning
confidence: 99%
“…25,26,29,31,32,34,39,[41][42][43]47,48,52,56,58,59,61,62 15 (46.9) 9 (60) 11 ( Face-to-face and telephone 27,28,30,33,[35][36][37]40,[44][45][46]51,53,54,57,63 13 ( 25,27,28,31,34,36,[40][41][42][43][44][45][46][47][48][49][50]53,…”
Section: Summary and Best-designed Studiesmentioning
confidence: 99%
See 2 more Smart Citations